REBUILDING SELF-ESTEEM DURING COMMUNITY-BASED DRUG REHABILITATION IN INDONESIA: A PHENOMENOLOGICAL STUDY OF POWER, VIRTUE, COMPETENCE, AND SIGNIFICANCE IN IBM CLIENTS - Sinta Almaidah; Arri Handayani; Siti Fitriana (CV. TOTUS TUUS, 2026)
Community-based drug rehabilitation programs expose clients to everyday social realities, including stigma, peer pressure, and family dynamics, which may shape how self-esteem is rebuilt during recovery. Yet, research on self-esteem in community-based intervention contexts remains limited compared with studies in formal rehabilitation institutions. This study aimed to explore the meaning of self-esteem among clients undergoing rehabilitation in a Community-Based Intervention (IBM) program in an Indonesian village, using Coopersmith’s framework (power, virtue, competence, and significance). A qualitative phenomenological design was employed. Two IBM clients who had participated in rehabilitation for more than three months were selected, and data were collected through in-depth interviews, supplemented by triangulation with family members and recovery agents. Data were analyzed using Miles and Huberman’s procedures (data reduction, display, and conclusion drawing). The findings revealed four interrelated themes: power (variations in self-control and relapse-prevention strategies), virtue (uneven moral–religious change facilitated by mentoring), competence (growth in technical and/or social skills linked to confidence and reintegration), and significance (self-worth shaped by family support, community acceptance, and shifts in stigma). The study concludes that self-esteem in IBM clients is not merely an internal trait but is co-constructed through psychological regulation, skill development, and social recognition within the community ecology. Practically, IBM services should integrate structured self-esteem strengthening through relapse-management coaching, competency training, and stigma-reduction initiatives involving families and local communities. Future research should involve larger samples, longitudinal designs, and comparative analyses across community versus institutional rehabilitation settings.